Predicament in construction – an overlook to delays, cost overruns and risks - Ahmad Aiman Ariff, Ahmad Zamri (2019)
Time and cost performance are the basic criteria for the success of any project. These problems in the construction industry are a global phenomenon. Malaysia has been regarded as an industry facing poor performance leading to failure in achieving effective time and cost performance. As a consequence, most projects face huge amount of time or delays and cost overruns. This study assessed the delay and cost of overruns of construction projects in Malaysia and identified relevant ways to minimize deferred costs, delays and risks involved in construction projects. The major contributors to this poor performance include design problems or errors in resource, poor management of material, the weather condition, unpunctually material delivery and unavailability of incentives for contractor for finishing ahead of schedule. Furthermore, interviews were conducted with experienced personnel involved in managing construction projects in order to comprehend the situations encountered during the cycle life of the project. This study provide insight overviews of the current practice such that can be used as preventive measures for future projects.